Financiamento habitacional no Brasil - Rossbach, Anacláudia Marinheiro Centeno (2005)
This paper analyses the housing finance system adopted in Brazil. From a historic perspective, issues like funding sources, legal framework, main agents and recent development had been detailed. The main housing finance systems existing in the world are specified in the first chapter: the savings deposits, contract savings, mortgage bonds, housing banks and the secondary market for mortgages. The second chapter refers just to the secondary market for mortgages in the United States. In the third chapter we analyze specifically the recent developments of the Brazilian housing finance system. In Brazil mortgage finance is made by the financial institutions in order to fulfill the legal requirements from the strong regulation of the savings linked system, known as Sistema Brasileiro de Poupança e Empréstimo, SBPE and from the federal pension severance guarantee fund, known as Fundo de Garantia por Tempo de Serviço, FGTS. The initiative of creating a secondary market for mortgages, through the Sistema de Financiamento Imobiliário or SFI, is still very incipient. Two basic pre conditions are missing in Brazil to consolidate this system: positive macroeconomic environment, with low market interest rates; and a developed, solid and efficient primary mortgage market. For many years the macroeconomic environment consisted of high inflation and interest rates, which functioned as barriers for the mortgage market development. Today, as an effect from the high market interest rates, the mortgage business is not attractive either for the borrower or for the lenders. The demand for mortgage credit must get adapted to the existing products in an oligopoly financial market, which excludes the majority of the Brazilian families, whose income is not sufficient to access a credit, and contributes to improve the informal sector.